Enhancing the Efficiency of Polymer Solar Cells by Modifying Buffer Layer with N,N-Dimethylacetamide - Shaopeng Yang; Xuefeng Sun; Ye Zhang; Guang Li; Xiaohui Zhao; Xiaowei Li; Guangsheng Fu (International Journal of Photoenergy)
We modified the PEDOT:PSS anode buffer layer in P3HT:PCBM bulk heterojunction polymer solar cells by spin-coating the solvent N,N-dimethylacetamide (DMAC). This modification significantly enhanced the efficiency of the ITO/PEDOT:PSS/DMAC/P3HT:PCBM/LiF/Al solar cells. The DMAC-treated device spin-coated at 3000 rpm exhibited a power conversion efficiency (PCE) of 3.74%, a 59% improvement over that of an untreated cell. To study the mechanism of improving the conversion efficiency, we characterized many parameters, including the light and dark I-V curves, external quantum efficiency, active layer absorption spectrum, transmission spectrum of ITO:PEDOTPSS, PEDOT:PSS surface morphology, and electrical conductivity. Modifying the PEDOT:PSS film increased conductivity, making it more conducive to hole extraction and collection. Our findings suggest that modifying the anode buffer layer can improve photoelectric conversion efficiency.